(untitled) (Annals of Medical Research, 2021)
Aim: We aimed to compare hemogram parameters (especially platelet indices) in smoking patients with coronary artery ectasia and the normal coronary artery. Material and Methods: The records of 7287 patients who underwent coronary angiography between January 2017 and October 2019 were reviewed. After appropriate exclusions, smoking patients were divided into coronary artery ectasia and normal coronary artery groups. A total of 292 patients were included in the study and hemogram parameters of these two groups were compared.Results: Compared to the control group triglyceride cholesterol (136 (43-835) vs. 152 (30-835) mg/dL, p:0.030), Hemoglobin (14.6 (11.5-16.9) vs. 14.9 (11.5-17.1) gr/dL, p: 0.012), RDW (15.5 (12.9-19.9) vs. 15.2 (12.3-17.5) %, p: 0.016), Eosinophil count, (0.172 (0.002-0.877) vs. 0.143 (0.039-0.385) u/mm3, p: 0.035), Platelet counts (Plt) (226 (143-442) vs. 218 (125-294) k/mm3, p: 0.013), PDW (17.7 (16.1-20.9) vs. 17.5 (15.9-18.9) %, p: 0.003), MPV (8.2 (6.2-11.2) vs. 7.8 (6.1-10.6) Fl, p: 0.001), PCT (0.18 (0.07-0.32) vs. 0.17 (0.08-0.24), p: 0.017), NLR (2.1 (0.9-12.8) vs. 2.0 (1.1-4.5), p: 0.012), and PLR (102.8 (50.8-339.3) vs. 97.1 (46.0-194.3), p: 0.004), were significantly in CAE patients. There was no significant difference between the two groups in terms of other biochemical and hemogram values.Conclusion: Hemogram parameters that are common, simple and inexpensive are increased smoking patients with coronary artery ectasia.